2018
DOI: 10.1590/0034-7167-2017-0365
|View full text |Cite
|
Sign up to set email alerts
|

Board games: gerotechnology in nursing care practice

Abstract: Patented under registration no. BR 1020160107725, the game was created as a technological product based on the discussions with older adults, considering the conceptions, knowledge and practices shared by them about aging. Final considerations: The gerotechnology implemented in clinical nursing practices functioned as a playful resource to exercise self-determination and independence among older adults, boosting memory, self-esteem, socialization processes, exchanging experiences and shared learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
33

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 11 publications
0
30
1
33
Order By: Relevance
“…It is suggested that these (geronto)technologies be employed from the initial stage of the disease, as it is understood that the greater the cognitive stimulation of the old person, the greater the preservation of cognition or the slowing of neuronal degradation. Cognitive performance involves mental functioning, including perception, attention, memory, reasoning, decision making, problem solving and formation of complex structures of knowledge 18 , which suffer a considerable decline in the intermediate stage of AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that these (geronto)technologies be employed from the initial stage of the disease, as it is understood that the greater the cognitive stimulation of the old person, the greater the preservation of cognition or the slowing of neuronal degradation. Cognitive performance involves mental functioning, including perception, attention, memory, reasoning, decision making, problem solving and formation of complex structures of knowledge 18 , which suffer a considerable decline in the intermediate stage of AD.…”
Section: Discussionmentioning
confidence: 99%
“…There are some examples of games in the literature, such as a board game aimed at promoting active and healthy aging. This game acted like a playful pedagogical resource in nursing care, contributing to the construction of knowledge in the elderly health area 34 . Fernandes et al 35 described the development of a board game called "Family Nursing Game" aimed at nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Another study highlighted the creation and implementation of a board game aimed at promoting healthy active aging, revealing that the playful element (the game) acted as an exercise of selfdetermination and independence for the elderly improving the memory, self-esteem, socialization processes, exchange of experiences, and shared learning. 45 Physical exercise and mental health are listed as two examples that contribute to healthy active aging, deserving more attention from individuals, health professionals, and public policies. 46 A study is added to this category that addresses the lack of health promotion actions in Primary…”
Section: -6mentioning
confidence: 99%